A Semantic-Based Cognitive Training Programme on Everyday Activities: A Feasibility and Acceptability Study among Cognitively Healthy Older Adults. - Tulliani, Nikki; Bye, Rosalind; Bissett, Michelle; Coutts, Samantha; Liu, Karen P. Y. (Occupational Therapy International, 2023)
Background. During the normal ageing process, a person's cognitive functions and memory gradually decline, which can affect their ability to perform everyday activities including cooking, cleaning, managing finances, and shopping. Semantic memory encoding strategies benefit older adults' cognitive and functional performance. Such strategies can be taught by an accessible, cost-effective, and flexible app-based programme. Currently, no studies examine such an app-based programme focussed on everyday activities. Objectives. To determine if an app-based programme constructed on the principles of semantic memory encoding strategies, targeted towards older adults, called Enhancing Memory in Daily Life (E-MinD Life) is (1) feasible by examining acceptance, engagement, and attendance and (2) acceptable by examining the perceived effectiveness, relevancy, clarity, and convenience. Methods. Eleven participants were recruited to a nine-week (18 sessions) programme using E-MinD Life. Feasibility was measured by collecting data on recruitment and retention rates, attendance, and duration of sessions. Acceptability was measured via a Likert scale questionnaire and free comments. Likert scale responses were analysed using descriptive statistics; open-ended responses were categorised qualitatively via constant comparative approach. Results. Nine participants completed the programme. Overall, most participants found the programme relevant, convenient, logical, and easy to understand and perceived it to be effective to address functional cognitive problems impacting performance of everyday activities. The results from the qualitative analysis showed that participants found the programme enjoyable and the interaction with the research team throughout the intervention beneficial. Conclusion. E-MinD Life shows promise as the focus of further research to determine the effectiveness of the programme and sematic-based cognitive strategies in maintaining cognition and performance in everyday activities among older adults with and without cognitive impairment.